The SES-CD Could Be a Predictor of Short- and Long-Term Mucosal Healing After Exclusive Enteral Nutrition in Pediatric Crohn’s Disease Patients - Tang, Wenjuan; Hu, Wenhui; Shi, Peng; Ye, Ziqing; Wu, Jie; Zhang, Ye; Wang, Yuhuan; Huang, Ying (Frontiers in Pediatrics, 2022)
Aims: To explore the predictors of mucosal healing (MH) to exclusive enteral nutrition (EEN) in the short- and long-term in pediatric Crohn's disease (CD) patients. Methods: A retrospective analysis was performed for newly diagnosed active CD patients admitted from January 2017 to December 30, 2020 in our center and treated with EEN for inducing therapy with a minimum of 12 months of follow-up post EEN. According to the Simple Endoscopic Score for CD (SES-CD) at 1-year post-EEN, 17 patients with SES-CD<3 were classified into the sustained MH group (sMH), and 33 patients with SES-CD≥3 were classified into the sustained non-MH group (sNMH). Statistical methods were used to compare the differences between the 2 groups and explore the predictors of MH to EEN at EEN ending and 1-year post-EEN. Results: The SES-CD in the sMH group was lower than that in the sNMH group both at baseline and EEN ending (sMH vs. sNMH: 8.7 ± 1.2 vs. 16.2 ± 1.0 P <0.001 at baseline; 1.0(3.5) vs. 4.0(2.0) P<0.01 at EEN ending), The weighted Pediatric Crohn's Disease Activity Index, erythrocyte sedimentation rate in sMH group were lower than the sNMH group at baseline but no difference at EEN ending (both P<0.05). From baseline to 1-year post-EEN, compared with patients in the sNMH group, there were more patients with L1 in the sMH group at each time point (all P<0.001) and fewer patients with L3 in the sMH group at baseline and 1-year post-EEN. After EEN, fewer patients received infliximab and a longer time to infliximab exposure in the sMH group than in the sNMH group. Only SES-CD at baseline was negatively associated with MH at EEN ending (OR=1.40 95% CI=1.12-1.67, P=0.00) and 1-year post-EEN (OR=1.33, 95% CI=1.12-1.58, P=0.001), the cut off value was 11.5. Conclusion: SES-CD could predict MH to EEN both short- and long-term. Patients with SES-CD<11.5 have a high probability of reaching MH by EEN-inducing therapy and maintaining sustained MH at 1-year post-EEN. Patients with an SES-CD greater than 11.5 at baseline should be treated more aggressively with biologics.